2020
DOI: 10.3390/w12030813
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Extremes of Drought Episodes in Vietnam Sub-Regions during 1980–2017 at Different Timescales

Abstract: This study investigated the temporal occurrence of dry conditions in the seven climatic sub-regions of Vietnam during the 1980–2017 period. This assessment was performed using the Standardized Precipitation Evapotranspiration Index (SPEI) and the Standardized Precipitation Index (SPI) at 1 to 24 months timescales. Results show that the main periods of extreme drought occurred simultaneously throughout the country in 1992–1993 and 2003–2004, except for 2015–2016, when it was not identified in the southern regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…This indicates that the decreases in the SPI and SDI values are related to increases in the El Niño and PDO warm phases, and consequently rises in the possibility of meteorological and hydrological droughts. Similarly, Stojanovic et al (2020) also indicated negative correlations of meteorological drought with the ENSO and PDO in South Vietnam. Table 3 also shows that the meteorological drought has 7-month lag time from the ENSO and 8-month lag time from the PDO, and the hydrological drought has 8-month lag time from the ENSO and 9-month lag time from the PDO.…”
Section: Identification Of Historical Drought Characteristicsmentioning
confidence: 85%
See 1 more Smart Citation
“…This indicates that the decreases in the SPI and SDI values are related to increases in the El Niño and PDO warm phases, and consequently rises in the possibility of meteorological and hydrological droughts. Similarly, Stojanovic et al (2020) also indicated negative correlations of meteorological drought with the ENSO and PDO in South Vietnam. Table 3 also shows that the meteorological drought has 7-month lag time from the ENSO and 8-month lag time from the PDO, and the hydrological drought has 8-month lag time from the ENSO and 9-month lag time from the PDO.…”
Section: Identification Of Historical Drought Characteristicsmentioning
confidence: 85%
“…In the 2015/2016 drought alone, Vietnam had suffered an economic loss of approximately USD$ 674 million, accounting for about 0.35% of GDP in 2015(UNDP 2016. Recently, drought studies in Vietnam under climate change impacts have received considerable attentions; however, they are mainly focused on meteorological drought (Vu-Thanh et al 2014;Vu et al 2015b;Stojanovic et al 2020), and there is still limited knowledge of climate change impacts on the hydrological drought in Vietnam. Furthermore, the interaction between the global climate oscillation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the SPI (2006, 2012, and 2018) reported, three extremely wet events although only one was noted by the SPEI (2018). It should be noted that there is a disparity between SPI and SPEI results from 2017 to 2019, where the SPEI indicates the occurrence of only wet events This disparity between the indices occurs because of the increase in precipitation, the only variable that the SPI index takes into account, occurs before the decrease in temperature, a variable that the SPEI requires to calculate the climate water balance (Stojanovic et al, 2020). The SPI and SPEI values on a 6-month time scale oscillate between −2.5 and 2.0 ( Figure 5).…”
Section: Spi and Spei Indicesmentioning
confidence: 99%
“…It should be noted that although the SPEI values generally oscillated between −3.0 and 2.0, the 24-months SPEI is the only one that has presented values close to −3.0 ( Figure 7A), in comparison to other SPEI values at smaller scales. This may suggest that the importance of temperature and evapotranspiration is greater for longer time scales (Stojanovic et al, 2020).…”
Section: Spi and Spei Indicesmentioning
confidence: 99%
“…Spearman correlation is a non-parametric test. Both correlation methods are widely used to detect regional rainfall teleconnection with climate indices [10,43,45,52,54,55].…”
Section: Climate Indicesmentioning
confidence: 99%